Análisis, diseño, desarrollo e implementación de un sistema de gestión de adquisiciones para la Superintendencia de Control del Poder de Mercado - Montenegro Pillajo, Galo Daniel (2016)
The next job titling includes analysis, design, development and implementation of management system procurement for the Superintendencia de Control del Poder de Mercado, is an oriented web application that allows the management of purchases in order to automate its administrative processes by optimizing their information flows, thus enhancing the control and monitoring of its procurement procedures. In the first chapter the current situation of SCPM is described how currently purchases are managed and how through the implementation of the computer system can optimize, streamline and control the process of procurement management. Additionally, the justification and the project objectives outlined. In the second chapter discusses in general terms and concepts of procurement management systems, the theoretical basis of methodologies, programming languages, web technologies that are used directly in the construction phase of the system is broken. In the third chapter the construction of making a description of the class and relevant code and diagrams of the database and deployment are also presented system is specified. Testing and quality metrics applied to the finished software to check the efficiency and stability of the system by the black box testing and load testing. Finally, conclusions and recommendations leave the software development phases until completion of the web system are extracted.